Obstinate Star : A History of the Puerto Rico Independence Movement - Bernabe, Rafael (Historical Materialism Book Series, 2025)
Obstinate Star is a history of Puerto Rico's independence struggle against Spanish and U.S. colonialism. From the time of the Napoleonic Wars, it traces the movement's currents, within and beyond the island, linking them to ongoing social conflicts and international trends and conjunctures. Beginning with the radical democratic fight against Spanish control, it moves on to the early reactions to U.S. rule, the role of Nationalism, Communism and New Deal currents during the Great Depression and the Second World War, the rise of new forces in the wake of the Cuban revolution and recent struggles in the epoch of capitalist globalisation.